Citizens Rights and Environmental Genocide - Carrizo, Cecilia (2012)
Within the framework of pragmatism and linguistic turn, the meaning of a word is embedded in the context where it is stated. The Mothers of Ituzaingo´ Neighborhood in the city of Córdoba, Argentina (Madres de Barrio Ituizaingo´ Anexo) is a case of citizens’ practices in defense of human life, health, and the environment. Doing research on their actions from the aforementioned perspective, we have found that all parties involved in the situation use the word ‘‘genocide,’’ for example, when the authorities, whose intervention are demanded and fail to act, deny the possibility of a genocide or when citizens claiming for their rights narrate their experience as ‘‘a genocide in disguise’’ (‘‘genocidio encubierto’’). The concept of genocide is brought up often by contamination victims throughout the world, even though this use does not match with the United Nations’ official definition, which refers to States’ actions and omissions that do not protect constitutional rights and laws. In this context, where there is a dispute over the situation’s nomination, we aim at investigating the experience of those affected in their interaction with state institutions, the latter being the ones questioned. Is it reasonable for the victims of environmental injustice to use ‘‘genocide’’ as a concept? From this research question, we have resorted to qualitative methodologies to achieve a deeper understanding of the speeches and practices in this inter-subjective context. In this article we present the systematization of said practices in two different ways, so-called citizenship stripping ways.